The preferred factors of accommodation among off-campus students / Nurul Hannan Nor Hizam and Nor Aini Salleh - Nor Hizam, Nurul Hannan; Salleh, Nor Aini (2023)
Due to the economic growth during the pandemic that has slowly recovered, college demand is high because most of the students prefer to stay on campus, but the supply of hostel accommodation for the students is low. The ultimate aim of this research is to identify the issues related to the preferred housing rental of off-campus students. Therefore, the objective of this research is to identify the preferred residential rental area among off-campus students. The population for this study is 1,208 off-campus students at Universiti Teknologi MARA, Seri Iskandar (UiTMSI). The sample size of this research is 292 respondents needed for data collection by using the simple random method. In order to answer the research question, the questionnaire has been distributed via Telegram and WhatsApp to off-campus students as primary data. Literature reviews that have been conducted are relevant to this topic and serve as secondary sources of information. The data collection has been analysed using Descriptive Analysis in SPSS Version 28.0. The finding reveals that the popular residential area is Bandar Seri Iskandar (SIDEC) because of its proximity to the campus. It is important for the Higher Education Institution (HEI) and government to set the standard requirements for the private market rental regarding the accommodation facilities so that the students will have the basic facilities with an affordable and comfortable residential rental.